##### apply the appropriated property to simplify the expression

 Mathematics Tutor: None Selected Time limit: 1 Day

exercise1. 6(2x)  exercise2. -3(12k) exercise3. 6(2 + x)   exercise4. -6(-1 - k) exercise5. -6 +(-1 - k)

exercise6. -8 + (4 - p) exercise7. -8 (4 - p)   exercise 8.   8(1/2 a )   exercise9. 8(1/2 + a )

exercise10.  5/9(9 + Y)    exercise11. 5/9(9y)

Oct 8th, 2014

exercise1. 6(2x) =6*2x = 12x

exercise2. -3(12k) = -3*12k = -36k

exercise3. 6(2 + x)  = 6*2+6*x= 12+6x

exercise4. -6(-1 - k) = -6*(-1)-k*(-6) = 6 + 6k

exercise5. -6 +(-1 - k) = -6 +(-1) + (-k) = -6 -1 -k

exercise6. -8 + (4 - p) = -8+4+(-p) = -4 -p

exercise7. -8 (4 - p)  = -8*4 -(-8)*p = -32 + 8p

exercise 8.   8(1/2 a ) = 8*1/2a = 4a

exercise9. 8(1/2 + a ) = 8*1/2 + 8*a = 4+8a

exercise10.  5/9(9 + Y)  =5/9*5 + 5/9*Y = 25/9 + 5/9y

exercise11. 5/9(9y) = 5/9 *9y = 5y

Oct 8th, 2014

...
Oct 8th, 2014
...
Oct 8th, 2014
Dec 10th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle